Automatic Indexing for Content Analysis of Whale Recordings and XML Representation. (3rd May 2010) - Bénard Bénard, Frédéric Frédéric; Glotin Glotin, Hervé Hervé
Abstract : This paper focuses on the robust indexing of sperm whale hydrophone recordings based on a set of features extracted from a real-time passive underwater acoustic tracking algorithm for multiple whales using four hydrophones. Acoustic localization permits the study of whale behavior in deep water without interfering with the environment. Given the position coordinates, we are able to generate different features such as the speed, energy of the clicks, Inter-Click-Interval (ICI), and so on. These features allow to construct different markers which allow us to index and structure the audio files. Thus, the behavior study is facilitated by choosing and accessing the corresponding index in the audio file. The complete indexing algorithm is processed on real data from the NUWC (Naval Undersea Warfare Center of the US Navy) and the AUTEC (Atlantic Undersea Test & Evaluation Center-Bahamas). Our model is validated by similar results from the US Navy (NUWC) and SOEST (School of Ocean and Earth Science and Technology) Hawaii university labs in a single whale case. Finally, as an illustration, we index a single whale sound file using the extracted whale's features provided by the tracking, and we present an example of an XML script structuring it.